Application of zwitterionic covalent organic framework solid-phase microextraction fiber in neurotransmitter analysis
By using ionic covalent organic framework materials prepared by ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phlogenetic glucosol, the problems of poor extraction selectivity and low enrichment efficiency in the prior art are solved, and efficient enrichment and extraction analysis of different polar neurotransmitters are achieved.
Patent Information
- Application Number
- CN202411915195.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The existing covalent organic framework materials have poor selectivity, low enrichment efficiency, low sensitivity, high detection limit and poor extraction effect on target substances in neurotransmitter extraction.
Ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phlogenetol were used as functional monomers to prepare ionic covalent organic framework material through Schiff base reaction, and self-assembled layer by layer by sol-gel coating to prepare ionic covalent organic framework solid phase microextractable fiber coating.
It realizes efficient enrichment and extraction analysis of different polar neurotransmitters in complex biological samples, improves the selectivity and enrichment efficiency of the analysis method, reduces the detection limit, and enhances the specific adsorption and enrichment ability of neurotransmitters.
Smart Images

Figure CN119684550A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical synthesis, chemical analysis and detection and sample pretreatment, and in particular to a preparation method and application of an ionic covalent organic skeleton solid phase microextraction fiber coating. Background Art
[0002] Neurotransmitters, as a class of endogenous chemical substances, are widely distributed in the central nervous system, brain tissue and body fluids of mammals. They play an important role in the physiological processes of intercellular communication and signal transduction in the human body. Abnormal changes in the content of neurotransmitters in the body are also closely related to diseases such as cancer, immune response and inflammation. They are expected to become new targets for the diagnosis and treatment of diseases such as cancer, and can also serve as potential biomarkers for these diseases. Therefore, the detection of trace neurotransmitters in biological fluids is of great significance to promote the detection of diseases and the development of new therapeutic drugs.
[0003] Currently, a variety of sample preparation techniques such as liquid-liquid extraction, solid phase extraction, dispersed liquid-liquid microextraction, magnetic solid phase extraction and solid phase microextraction are used for the enrichment and detection of neurotransmitters in various biological matrices. However, traditional pretreatment methods, such as solid phase extraction (SPE) and liquid-liquid extraction (LLE), require a large sample volume and organic solvent consumption, which is often limited in daily analysis, such as the analysis of solid tissue samples. Solid phase microextraction (SPME) technology not only has the advantages of fast sampling speed, small sample requirement, no need to consume a large amount of organic solvent, but also has the advantages of low invasiveness, minimal invasiveness, low cost and high throughput. It has been widely used in the extraction and enrichment of endogenous compounds and metabolites in complex biological matrices such as biological fluids and solid tissues. Covalent organic frameworks (COFs) are a class of innovative porous crystalline materials that mainly connect organic monomers together through covalent bonds to form 2D or 3D networks. COFs have large specific surface area, high porosity, good thermal stability and chemical stability, and have attracted widespread attention due to their great application potential in sensing, separation, catalysis, optoelectronics and biomedicine. At present, there have been reports on the use of covalent organic frameworks for neurotransmitter extraction, but the existing framework materials can only be used for a small amount of single neurotransmitters (such as catecholamines, or alkaline and acidic neurotransmitters), so it is necessary to develop functional materials that can extract multiple neurotransmitters at the same time. At the same time, the existing covalent organic frameworks have problems such as low enrichment efficiency and low sensitivity. Therefore, how to prepare a covalent organic framework solid phase microextraction fiber for improving the selectivity and enrichment efficiency of analytical methods for neurotransmitters is a hot and difficult problem that needs to be solved in this field. Summary of the invention
[0004] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an ionic covalent organic framework solid phase microextraction fiber and its preparation method and application, so as to solve the problems of poor selectivity between the covalent organic framework used for neurotransmitters in the prior art and analytes, low enrichment efficiency, low sensitivity, high detection limit and poor extraction effect on the target. The ionic covalent organic framework solid phase microextraction fiber prepared by the present invention realizes the efficient enrichment and extraction analysis of neurotransmitters of different polarities in complex biological sample matrices.
[0005] In order to achieve the above-mentioned purpose, the technical solution of the present invention is, on the one hand, to provide an application of an ionic covalent organic framework material in the preparation of an adsorbent for sample pretreatment, wherein the ionic covalent organic framework material is based on ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde pyroglobulin as functional monomers, acetic acid as a catalyst, and condensed through a Schiff base reaction to obtain an ionic covalent organic framework material.
[0006] Furthermore, the specific preparation method of the ionic covalent organic framework material is: accurately weigh ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol, mix, then add the reaction solvent, then add the acetic acid solution, and ultrasonically disperse. Subsequently, degas and seal through three freeze-pump-thaw cycles, and react. After the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash alternately with tetrahydrofuran, deionized water and acetone, and dry to obtain a deep red EB-Da-COF.
[0007] Furthermore, the molar ratio of ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol is 0.8-1.2:0.8-1.2:1.2-1.8.
[0008] Furthermore, the concentration of the acetic acid solution is 6M, and the ratio of the acetic acid solution to trialdehyde phloroglucinol is 0.5mL:0.45mmoL.
[0009] Furthermore, the reaction temperature is 110-120° C., the reaction time is 60-72 hours, and the reaction solvent is a mixed solution of 1,3,5-trimethylbenzene and 1,4-dioxane in a volume ratio of 2:3.
[0010] Furthermore, sample preparation includes extraction analysis for neurotransmitters in serum samples and brain tissue.
[0011] On the other hand, the technical solution of the present invention is to provide an application of an ionic covalent organic framework solid phase microextraction fiber as an adsorbent in sample pretreatment, wherein the fiber is based on nickel-titanium fiber filaments, and the ionic covalent organic framework material is coated on the fiber filaments by layer-by-layer self-assembly by a sol-gel coating method to obtain an ionic covalent organic framework solid phase microextraction fiber. Specifically, the following steps are included:
[0012] (1) Preparation of PAN glue: Weigh 4.5-5.0 g PAN and 72.5 mL N,N-dimethylformamide, mix, stir evenly, and seal and place at 90°C for 1 h;
[0013] (2) weighing 300.0-325.0 mg of the ionic covalent organic framework material, then adding 2.5-3.1 g of PAN glue, and then adding 0.15-0.2 g of propylene glycol, vortexing, and then stirring overnight to obtain an ionic covalent organic framework solid phase microextraction fiber coating;
[0014] (3) The ionic covalent organic framework solid phase microextraction fiber coating is coated on the fiber filament to obtain the ionic covalent organic framework solid phase microextraction fiber.
[0015] Furthermore, the coating length of the ionic covalent organic framework solid phase microextraction fiber is 4.5±2 mm and the thickness is 10±5 μm. The concentration of the mixed glue can be slightly adjusted according to the coating effect.
[0016] Furthermore, sample preparation was used for the extraction and analysis of neurotransmitters in serum samples and brain tissues.
[0017] Compared with the prior art, the present invention has the following excellent effects:
[0018] (1) The ionic covalent organic framework material prepared by the Schiff base reaction of the present invention has a simple preparation step, and the obtained material has good mechanical stability and thermal stability. It is connected by a relatively stable imine bond, which improves the service life of the extraction fiber.
[0019] (2) The present invention uses 2,5-diaminobenzoic acid with cation exchange function, ethidium bromide with anion exchange function, and trialdehyde pyroglutamic acid as functional monomers to prepare an ionic covalent organic skeleton, and further prepares it into a solid phase microextraction fiber coating. The prepared fiber coating has a uniform surface distribution and uniform thickness, and has a dense honeycomb porous structure, which greatly improves its adsorption and extraction capacity.
[0020] (3) The ionic covalent organic framework prepared by the present invention using 2,5-diaminobenzoic acid with cation exchange function, ethidium bromide with anion exchange function, and trialdehyde phloroglucinol as functional monomers has a large specific surface area (183.26 m 2 / g) and a narrow particle size distribution (average pore size of 2.27nm), so that it has a higher specific surface area, mesoporous structure and protein exclusion effect. The ionic covalent organic skeleton solid phase microextraction fiber coating prepared by the present invention has good biocompatibility and protein exclusion ability, so that it can be directly used for the extraction of target substances in biological samples without the need for a protein precipitation step.
[0021] (4) In addition to having good hydrophilicity, the ionic covalent organic skeleton solid phase microextraction fiber coating prepared by the present invention is rich in functional groups such as hydroxyl, carboxyl, phenyl and quaternary ammonium in its structure, which can interact with the target analyte through ion exchange, π-π stacking, hydrogen bonding and hydrophilic-hydrophobic interaction, showing strong specific adsorption and efficient enrichment ability for neurotransmitters.
[0022] (5) The three monomers (2,5-diaminobenzoic acid, ethidium bromide and trialdehyde phloroglucinol) of the present invention have cheap and readily available raw materials, short synthesis steps, simple operation, mild reaction conditions and high synthesis yield, and are suitable for large-scale preparation and promotion.
[0023] (6) The ionic covalent organic framework solid phase microextraction fiber coating prepared by the present invention has good stability and reusability, can ensure the efficiency and reliability of the extraction process, and shows significant advantages in saving resources, reducing costs and protecting the environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 These are scanning electron microscope images of the zwitterionic covalent organic framework (A) prepared in Example 1 of the present invention, a local portion of the surface of the zwitterionic covalent organic framework solid phase microextraction fiber (B and C), and a cross-section of the zwitterionic covalent organic framework solid phase microextraction fiber coating (D).
[0025] Figure 2 This is the EDS element distribution spectrum of the ionic covalent organic framework prepared in Example 1 of the present invention.
[0026] Figure 3 This is a Fourier transform infrared spectrum of the ionic covalent organic framework prepared in Example 1 of the present invention.
[0027] Figure 4 The XPS overall spectrum (A) and detailed spectra of C (B), N (C) and O (D) of the ionic covalent organic framework prepared in Example 1 of the present invention.
[0028] Figure 5 This is a water contact angle test graph of the ionic covalent organic framework prepared in Example 1 of the present invention.
[0029] Figure 6 This is the N2 adsorption-desorption isotherm of the ionic covalent organic framework prepared in Example 1 of the present invention.
[0030] Figure 7 Comparison of the extraction efficiency of the target substance by ionic covalent organic framework fiber coating materials prepared with different monomers and commercial coatings.
[0031] Figure 8This is a diagram showing the macromolecular exclusion effect of the ionic covalent organic framework and solid phase microextraction fiber coating prepared in Example 1 of the present invention.
[0032] Fig. 9 This is a diagram showing the effect of the number of times the ionic covalent organic framework solid phase microextraction fiber coating prepared in Example 1 of the present invention can be reused. DETAILED DESCRIPTION
[0033] The present invention is further described below in conjunction with the embodiments, and the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The present invention is described in detail below with reference to specific embodiments.
[0035] Selection of UPLC-MS / MS conditions
[0036] Chromatographic conditions: Thermo Ultimate 3000 ultra-high performance liquid chromatography detection system (Thermo Fisher Scientific) and Phenomenex Kinetex C18 (100×3 mm, 2.6 μm) chromatographic column were used for chromatographic separation. The column temperature was 40°C, and 0.1% formic acid water (A) and 0.1% formic acid acetonitrile (B) were used as the mobile phases. The gradient was: 0-2 min, 2% B; 5-7 min, 2%-95% B; 7-7.5 min, 95%-2% B; 7.5-11 min, 2% B. The flow rate was 0.2 mL / min, and the injection volume was 5 μL.
[0037] Mass spectrometry conditions: TSQ Altis high-resolution mass spectrometer (Thermo Fisher Scientific), ion source H-ESI, MRM scanning mode, source area condition parameters: positive ion source voltage 3500V, negative ion source voltage 2800V, capillary temperature 325°C, heating temperature 325°C; sheath gas 30Arb, auxiliary ventilation 10Arb, backflush gas 0, nitrogen was used as collision gas and C-trap damping gas. The optimized parameters of MRM scanning are shown in Table 1:
[0038] Table 1 Basic chemical parameters such as LogP and PKa of target neurotransmitters and optimized conditions of MRM
[0039]
[0040]
[0041] Example 1: Preparation of SPME Fiber
[0042] (1) Preparation of zwitterionic covalent organic framework (EB-Da-COF) materials
[0043] Ethidium bromide (0.3mmoL), 2,5-diaminobenzoic acid (0.3mmoL) and trialdehyde phloroglucinol (0.45mmoL) were accurately weighed and mixed, and then 5mL of a mixed solution of 1,3,5-trimethylbenzene and 1,4-dioxane (2:3, v / v) was added, and then 0.5mL of a 6M acetic acid solution was added, and the mixture was ultrasonically dispersed for 10 minutes. Subsequently, it was degassed and sealed through three freeze-pump-thaw cycles, and reacted at 120°C for 72 hours. After the reaction was completed, it was cooled to room temperature, and the precipitate was collected by centrifugation, washed alternately with tetrahydrofuran, deionized water and acetone, and repeated 3 times, and then dried in a vacuum drying oven at 80°C for 12 hours to obtain a deep red zwitterionic covalent organic framework material (yield of about 90%).
[0044] In addition, the preparation steps of Da-COF are as follows: 2,5-diaminobenzoic acid (0.6 mmoL) and trialdehyde phloroglucinol (0.45 mmoL) are accurately weighed and mixed, and the subsequent preparation method is the same as that of EB-Da-COF.
[0045] The preparation steps of EB-COF are as follows: ethidium bromide (0.6 mmoL) and trialdehyde phloroglucinol (0.45 mmoL) are accurately weighed and mixed, and the subsequent preparation method is the same as that of EB-Da-COF.
[0046] (2) Preparation of fiber
[0047] At room temperature, the nickel-titanium fiber wire with a diameter of 0.3 mm was cut into several fiber metal wires with a length of 6.5 cm, and the cut ends of the fiber wires were polished with a grinding wheel to ensure that the cut ends of the fibers were smooth, which was conducive to the subsequent coating of the adsorbent material. After cutting and polishing, the fiber wires were repeatedly washed three times with a mixed solution of methanol, isopropanol and water in a volume ratio of 3:3:4 to remove grease and stains on the surface, and then dried in a 60°C oven for use.
[0048] (3) Preparation of polyacrylonitrile (PAN) glue
[0049] Take 5.0g PAN and add it to a 100mL wide-mouth bottle with a lid. Add 72.5mL N,N-dimethylformamide, and then use a glass rod to stir to evenly disperse the PAN. Cover the lid and shake it to make it uniform. Seal it and place it in a 90℃ oven for 1h. Open the lid every 15min to release air.
[0050] (4) Preparation of SPME fiber
[0051] Weigh 325.0 mg of ionic covalent organic framework material into a 5 mL glass bottle with a lid, add a magnet, add 3.1 g of PAN glue to the bottle, then add 0.2 g of glycerol, cover the lid and vortex for 10 minutes, then stir magnetically overnight for use. The SPME fiber was prepared by sol-gel coating method, and the coating was repeatedly coated by a pull-up coating machine until the coating on the fiber reached the desired thickness. The coating length was 4.5 mm and the thickness was 10 μm. The prepared SPME fiber was sealed and stored for use. The fiber was activated with methanol water in a volume ratio of 1:1 for 30 minutes before use.
[0052] Example 2: Preparation of SPME Fiber
[0053] (1) Preparation of zwitterionic covalent organic framework materials (EB-Da-COF)
[0054] Ethidium bromide (0.3mmoL), 2,5-diaminobenzoic acid (0.3mmoL) and trialdehyde phloroglucinol (0.3mmoL) were accurately weighed and mixed, followed by the addition of 3.5mL of a mixed solution of 1,3,5-trimethylbenzene and 1,4-dioxane (2:3, v / v), and then 0.5mL of a 6M acetic acid solution, and the mixture was ultrasonically dispersed for 10min. Subsequently, the mixture was degassed and sealed through three freeze-pump-thaw cycles, and reacted at 110°C for 60h. After the reaction, the precipitate was cooled to room temperature, collected by centrifugation, and washed alternately with tetrahydrofuran, deionized water and acetone. After repeating 3 times, it was dried in a vacuum oven at 80°C for 12h to obtain a deep red EB-Da-COF (yield of about 90%).
[0055] (2) Preparation of fiber
[0056] At room temperature, the nickel-titanium fiber wire with a diameter of 0.3 mm was cut into several fiber metal wires with a length of 6.5 cm, and the cut ends of the fiber wires were polished with a grinding wheel to ensure that the cut ends of the fibers were smooth, which was conducive to the subsequent coating of the adsorbent material. After cutting and polishing, the fiber wires were repeatedly washed three times with a mixed solution of methanol, isopropanol and water in a volume ratio of 3:3:4 to remove grease and stains on the surface, and then dried in a 60°C oven for use.
[0057] (3) Preparation of polyacrylonitrile (PAN) glue
[0058] Take 4.5g PAN and add it to a 100mL wide-mouth bottle with a lid. Add 72.5mL N,N-dimethylformamide, and then use a glass rod to stir to evenly disperse the PAN. Cover the lid and shake it to make it uniform. Seal it and place it in a 90℃ oven for 1 hour. Open the lid every 15 minutes to release air.
[0059] (4) Preparation of SPME fiber
[0060] Weigh 300.0 mg of ionic covalent organic framework material into a 5 mL glass bottle with a lid, add a magnet, add 2.5 g of PAN glue to the bottle, then add 0.15 g of glycerol, cover the lid and vortex for 10 min, then stir magnetically overnight for use. The SPME fiber was prepared by the sol-gel coating method, and the coating was repeatedly coated using a pull-up coating machine until the coating on the fiber reached the desired thickness. The coating length was 3.5 mm and the thickness was 15 μm. The prepared SPME fiber was sealed and stored for use. The fiber was activated with methanol water in a volume ratio of 1:1 for 30 min before use.
[0061] Example 3: Preparation of SPME Fiber
[0062] (1) Preparation of zwitterionic covalent organic framework materials (EB-Da-COF)
[0063] Ethidium bromide (0.3mmoL), 2,5-diaminobenzoic acid (0.3mmoL) and trialdehyde phloroglucinol (0.45mmoL) were accurately weighed and mixed, and then 5mL of 1,3,5-trimethylbenzene and 1,4-dioxane (2:3, v / v) mixed solution was added, and then 0.5mL of 6M acetic acid solution was added, and the mixture was ultrasonically dispersed for 10min. Subsequently, it was degassed and sealed through three freeze-pump-thaw cycles, and reacted at 120℃ for 72h. After the reaction, the precipitate was cooled to room temperature, collected by centrifugation, washed alternately with tetrahydrofuran, deionized water and acetone, and repeated 3 times, and dried in a vacuum drying oven at 80℃ for 12h to obtain dark red EB-Da-COF (yield of about 90%).
[0064] (2) Preparation of fiber
[0065] At room temperature, the nickel-titanium fiber wire with a diameter of 0.3 mm was cut into several fiber metal wires with a length of 6.5 cm, and the cut ends of the fiber wires were polished with a grinding wheel to ensure that the cut ends of the fibers were smooth, which was conducive to the subsequent coating of the adsorbent material. After cutting and polishing, the fiber wires were repeatedly washed three times with a mixed solution of methanol, isopropanol and water in a volume ratio of 3:3:4 to remove grease and stains on the surface, and then dried in a 60°C oven for use.
[0066] (3) Preparation of polyacrylonitrile (PAN) glue
[0067] Take 5.0g PAN and add it to a 100mL wide-mouth bottle with a lid. Add 72.5mL N,N-dimethylformamide, and then use a glass rod to stir to evenly disperse the PAN. Cover the lid and shake it to make it uniform. Seal it and place it in a 90℃ oven for 1 hour. Open the lid every 15 minutes to release air.
[0068] (4) Preparation of SPME fiber
[0069] Weigh 310.0 mg of ionic covalent organic framework material into a 5 mL glass bottle with a lid, add a magnet, add 3.0 g of PAN glue to the bottle, then add 0.2 g of glycerol, cover the lid and vortex for 10 min, then stir magnetically overnight for use. The SPME fiber was prepared by sol-gel coating method, and the coating was repeatedly coated by a pull-up coating machine until the coating on the fiber reached the required thickness. The coating length was 6.5 mm and the thickness was 5 μm. The prepared SPME fiber was sealed and stored for use. The fiber was activated with methanol water in a volume ratio of 1:1 for 30 min before use.
[0070] Example 4: Characterization of Zwitterionic Covalent Organic Framework Solid Phase Microextraction Fiber Coating
[0071] The morphology of the zwitterionic covalent organic framework solid phase microextraction fiber coating prepared in Example 1 was characterized by scanning electron microscopy. Figure 1 As shown, they are zwitterionic covalent organic framework materials ( Figure 1 A), Local view of the surface of the prepared zwitterionic covalent organic framework solid phase microextraction fiber ( Figure 1 B and 1C) and cross-sectional view of zwitterionic covalent organic framework solid phase microextraction fiber coating ( Figure 1 D) From Figure 1 A shows that the zwitterionic covalent organic framework is composed of a large number of fluffy linear villi-like structures, and its fluffy structural characteristics provide it with a large specific surface area and rich porosity. Figure 1 B and 1C, it can be seen that the surface of the prepared extraction fiber is uniformly rough, and the coating surface is evenly distributed, showing a porous structure of varying sizes. Figure 1 D indicates that the coating thickness is uniform, which is beneficial to increase the specific surface area of the coating to form more adsorption sites, and is also beneficial to the internal mass transfer between the target analyte and the coating material, which helps the rapid adsorption and desorption of neurotransmitter molecules.
[0072] Elemental analysis was used to analyze the C, N and O elements of the zwitterionic covalent organic framework material. The results are as follows Figure 2 As shown, the three elements C, N and O are evenly distributed in the covalent organic framework material, and their contents are 74.64%, 10.87% and 14.49%, respectively, indicating that the covalent organic framework material was successfully prepared.
[0073] The functional groups of EB-Da-COF were analyzed by infrared spectroscopy (FT-IR). Figure 3 As shown in the infrared spectra of 2,5-diaminobenzoic acid (Da) and ethidium bromide (EB), a peak at 3295 cm -1and 3158cm -1 The characteristic absorption peak of -NH2 near the wavelength is different from that at 3387cm in the infrared spectrum of 2,5-diaminobenzoic acid. -1 The absorption peak due to the stretching vibration of OH in -COOH appears at a wavelength of 1148 cm -1 The CO stretching vibration absorption peak near the wavelength and at 671 cm -1 The C=O bending vibration absorption peak at wavelength. In the infrared spectrum of ethidium bromide, there is a peak at 1404cm -1 The characteristic peaks of quaternary ammonium at wavelengths and 1256 cm -1 The CN absorption characteristic peak at 1075 cm -1 The methyl bending vibration absorption peak of ethidium bromide is near 2895 cm-1. -1 The characteristic absorption peak of HC=O in the aldehyde group appears near the wavelength and is located at 1645cm -1 Unlike ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol, the C=O absorption peak at 3295 cm-1 in the infrared spectrum of EB-Da-COF is -1 and 3158cm -1 The characteristic absorption peak of -NH2 near the wavelength and 1645cm -1 The characteristic peak of C=O absorption peak near the wavelength disappears, and the peak at 1577cm -1 A new C=N absorption peak appeared near the wavelength, indicating the formation of an imine bond. In addition, a peak at 1256 cm -1 The CN absorption characteristic peak at 1075 cm -1 The methyl bending vibration absorption peak near the wavelength and the C=O bending vibration absorption peak at 671cm -1 The above results indicate that EB-Da-COF was successfully synthesized via the Schiff base reaction between 2,5-diaminobenzoic acid, ethidium bromide and trialdehyde phloroglucinol.
[0074] The elemental composition of EB-Da-COF was analyzed by XPS. Figure 4 As shown in A, there are C, N and O elements in the ionic covalent organic framework. C1s spectrum ( Figure 4 In B), the characteristic peaks of CN, CO, C=N and CC bonds appeared at 287.63eV, 285.79eV, 284.77eV and 284.12eV, indicating the existence of imine bonds and the Schiff base reaction between monomers. Figure 4In C), characteristic peaks of C=N bonds also appear at 399.43 eV and 399.03 eV, and a quaternary ammonium group (-NR4) appears at 400.92 eV. + The characteristic peaks of EB-Da-COF indicate the presence of ethidium bromide. Figure 4 D) shows a significant peak at 531.89 eV formed by the carbonyl C=O / OC=O bond in -COOH, further indicating the successful introduction of 2,5-diaminobenzoic acid into EB-Da-COF. In summary, combined with the FT-IR results, the successful synthesis of the ionic covalent organic framework is further demonstrated.
[0075] Since EB-Da-COF has abundant hydrophilic groups such as -OH and -COOH, it is speculated that it may have certain hydrophilicity. Figure 5 The contact angle results show that the water contact angle of EB-Da-COF is 50.0°, indicating that EB-Da-COF has good hydrophilicity. This good hydrophilicity makes EB-Da-COF conducive to the extraction and enrichment of neurotransmitters (NTs) with greater polarity.
[0076] The specific surface area and pore properties of EB-Da-COF were determined by Brunauer-Emmett-Teller (BET) gas phase adsorption method. Figure 6 As shown in the figure, the N2 adsorption isotherm of EB-Da-COF is basically a type IV curve, indicating that EB-Da-COF mainly has a mesoporous structure with a pore size range of 2 to 50 nm. According to the pore size distribution measured by the BJH method, its average pore size is 2.27 nm and the particle size distribution is narrow. In addition, the specific surface area and pore volume of EB-Da-COF are 183.26 m 2 / g and 0.36cm 3 / g, so the higher specific surface area and mesoporous structure of EB-Da-COF give it better adsorption performance and protein exclusion effect.
[0077] Example 5: Investigation of the extraction and enrichment effect of SPME fiber on neurotransmitters of different polarities
[0078] In order to investigate the extraction effect of the prepared EB-COF, Da-COF and EB-Da-COF with three commercial adsorbents (HLB, PXC and C18) on the target neurotransmitters, the extraction conditions were as follows: the prepared SPME fiber was immersed in PBS buffer containing a certain concentration of neurotransmitters (γ-aminobutyric acid GABA, glutamine Gln, glutamate Glu, choline Cho, glycine Gly, tyrosine Tyr, threonine Thr, ornithine Orn, serine Ser, tryptophan Try, methionine Met, arginine Arg, 5-hydroxytryptamine 5-HT, dopamine DA, thyroid stimulating hormone TSH, histidine His, epinephrine E, norepinephrine NE, melatonin 5-MT), and the extraction was performed by shaking for 30 minutes, and then desorbed for 30 minutes for UPLC-MS / MS acquisition and analysis, and each fiber was repeated 3 times. The amount and number of analytes extracted by the fiber were analyzed by UPLC-MS / MS acquisition data to evaluate the extraction efficiency of different coatings. The results were normalized to the best extraction coating for each analyte and expressed as a percentage. Figure 7 As shown in A, the prepared ion exchange EB-Da-COF has a significantly higher extraction efficiency and a wider extraction coverage than EB-COF and Da-COF developed by combining other monomers; Figure 7 As shown in Figure 2, compared with the fibers coated with commercial adsorbents (HLB, PXC and C18), the prepared EB-Da-COF fibers have higher adsorption efficiency and coverage for these polar compounds, which is related to its multiple adsorption forces such as anion exchange, cation exchange, π-π stacking, hydrogen bonding and hydrophilic-hydrophobic interaction.
[0079] Example 6: Investigation of macromolecular exclusion performance
[0080] The protein exclusion performance of the ionic covalent organic framework material and ionic covalent organic framework solid phase microextraction fiber prepared in Example 1 was studied. The specific case is as follows: 2 mg EB-Da-COF material and 5 SPME fibers were added or immersed in mouse serum containing a concentration of 100 μg / mL selected protein and diluted with PBS buffer, and then the mixed solution was oscillated at 500 rpm at room temperature for 2 hours. Finally, the EB-Da-COF material and SPME fiber were separated respectively. The concentration change of macromolecular protein in the supernatant was analyzed at a wavelength of 280 nm using an ultraviolet spectrophotometer. The calculation formula of protein exclusion rate is: protein exclusion rate = Cs / C0×100%, where Cs is the concentration of the remaining macromolecules in the solution after adsorption of EB-Da-COF material, and C0 is the initial concentration in the solution. Firstly, albumin, which accounts for about 50% of the total plasma protein, was selected as the exclusion object, and the exclusion rates of EB-Da-COF and SPME fiber were investigated at albumin concentrations of 100μg / mL, 200μg / mL and 300μg / mL.
[0081] The results are as follows Figure 8 As shown in Figure A, as the albumin concentration gradually increased, the protein exclusion rate of EB-Da-COF and SPME fiber remained as high as over 87%. In addition, considering the complexity of the matrix in serum, the exclusion rates of EB-Da-COF and SPME fiber were investigated using hemoglobin, β-lactoglobulin and mouse serum at a concentration of 100 μg / mL as exclusion objects. The results are shown in Figure A. Figure 8 As shown in B, the exclusion efficiency of EB-Da-COF and SPME fibers for the two selected proteins and serum samples was still as high as over 90%. The above results show that EB-Da-COF and SPME fibers can greatly reduce the matrix interference caused by macromolecules such as proteins and can be directly used for the extraction and analysis of NTs in complex biological samples.
[0082] Example 7: Evaluation of the Reusability of SPME Fibers
[0083] The repeated practicality of the zwitterionic covalent organic framework solid phase microextraction fiber coating prepared in Example 1 is investigated, and the specific case is as follows:
[0084] The SPME fiber was subjected to repeated adsorption-desorption for Tyr, Glu, Cho, DA, 5-MT and His. After each extraction cycle, the SPME fiber was repeatedly washed with 1% FA+H2O / MeOH / CAN (40:30:30, v / v / v), MeOH (methanol), CAN (acetonitrile) and water. Fig. 9As shown in the figure, after 7 to 8 cycles, the intensity of the target was observed to decrease significantly. The relative standard deviations of the relative intensities of the six targets in 8 cycles were 3.29% (Tyr), 0.14% (Glu), 0.18% (Cho), 1.09% (DA), 1.30% (5-MT) and 6.15% (His), respectively, indicating that the adsorption efficiency of the SPME fiber gradually decreased with the increase in the number of uses. This phenomenon indicates that the SPME fiber can be reused within 8 cycles. In addition, as the number of uses increases, it can be observed that the SPME fiber swells PAN due to repeated contact with organic solvents. The above results show that the repeated use of SPME is inseparable from the stability of the EB-Da-COF structure.
[0085] Example 8: SPME Detection and Analysis Method Verification of Neurotransmitters in Serum Samples
[0086] A specific example of applying the ionic covalent organic framework solid phase microextraction fiber in Example 1 to the determination of neurotransmitters in mouse serum samples is as follows:
[0087] Take 200 μL of mouse serum sample and dilute it to 1 mL with PBS buffer and place it in a sample injection vial. Then immerse the prepared SPME fiber coating end in the diluted serum sample. After oscillating extraction for 30 minutes, wash the SPME fiber with ultrapure water for 10 seconds to remove impurities such as inorganic salts and insoluble pollutants on the surface. Subsequently, 100 μL of 1% FA (formic acid) + H2O / ACN / MeOH (4:3:3, v / v / v) mixed solvent was used to oscillate and desorb the neurotransmitters adsorbed on the SPME fiber. After desorption for 10 minutes, the SPME fiber was removed and the eluted solution was analyzed by UPLC-MS / MS.
[0088] Through the above operations, the established detection and analysis method was methodologically verified. The results are shown in Tables 2 and 3. This method has low detection limits and quantification limits for 19 NTs, and has good linear correlation (r 2 The results show that the SPME fiber coating of the present invention combined with ultra-high liquid chromatography-mass spectrometry has good accuracy and precision in the extraction and detection of neurotransmitters in serum, and realizes the application of ionic covalent organic framework solid phase microextraction fiber-ultra-high liquid chromatography-tandem mass spectrometry in the detection of neurotransmitters of different polarities in serum, and has good application effect.
[0089] Table 2 Methodological parameters for the detection of NTs in serum by ionic covalent organic framework solid phase microextraction-ultra-high performance liquid chromatography-tandem mass spectrometry
[0090]
[0091]
[0092] “*” and “#” represent the concentration units μg / mL and ng / mL, respectively. “x” and “y” represent the concentration of the target substance and the detected peak area, respectively.
[0093] Table 3 Precision and accuracy of NTs in serum by ionic covalent organic framework solid phase microextraction-ultra-high performance liquid chromatography-tandem mass spectrometry
[0094]
[0095] “*” represents the spiked concentrations of low, medium and high levels, which are 1, 25 and 50 μg / mL respectively; “#” represents the spiked concentrations of low, medium and high levels, which are 5, 25 and 100 ng / mL respectively.
[0096] Example 9: SPME fiber for in situ collection and analysis of neurotransmitters in mouse brain
[0097] The specific case of applying the ionic covalent organic framework solid phase microextraction fiber in Example 1 to in situ sampling and analysis of neurotransmitters in the mouse brain is as follows:
[0098] Methodological verification in brain substitute matrix: Agar was first dissolved in PBS buffer to prepare agar gel (2% agar, w / v). Then the sheep brain was thawed, and an appropriate amount of sheep brain was placed in a 2 mL grinding tube, clean stainless steel beads were added, and the sheep brain sample was pulverized on a TissueMaster at a frequency of 50 Hz. TM Homogenize in a high-throughput tissue grinder for 2 min to obtain brain homogenate. Agar gel and sheep brain homogenate were mixed at a ratio of 1:1 (w / v) to obtain brain substitute matrix. Methodological validation was performed by adding different concentrations of target neurotransmitters to 500 μL of substitute matrix.
[0099] Through the above operations, the established detection and analysis method was validated. Tables 4 and 5 are the methodological parameters and precision and accuracy results of SPME fiber for mouse brain neurotransmitter analysis. From the data results (Table 4), it can be seen that all analytes have good linearity (r 2>0.97) and a lower limit of quantification. Six groups of samples with the same concentration were analyzed continuously within one day, and the RSD% was between 6.10% and 14.87%. The matrix effect of the method was investigated by extracting and analyzing the blank surrogate brain matrix with the analyte added, and comparing the signal of each analyte at three concentration levels in the solvent (1% FA+H2O / ACN / MeOH (4:3:3, v / v / v)). The matrix effect fluctuated in the range of 80.20% to 119.48%. This shows that the method can be applied to the in situ sampling analysis of neurotransmitters and can be applied to the determination of actual samples. The precision of the method was evaluated by the RSD of repeated measurements at three concentration levels. The results are shown in Table 5. The precision was between 2.51% and 19.68%, and the accuracy was between 80.37% and 122.07%. The above results indicate that the fiber coating combined with ultra-high performance liquid chromatography-mass spectrometry has good accuracy and precision in the extraction and detection of neurotransmitters in brain tissue, indicating that this method can be applied to the in situ extraction and analysis of NTs in brain tissue.
[0100] Table 4 Methodological parameters for the detection of neurotransmitters in brain tissue by ionic covalent organic framework solid phase microextraction-ultra-high performance liquid chromatography-tandem mass spectrometry
[0101]
[0102]
[0103] “*” and “#” represent the concentration units μg / mL and ng / mL, respectively. “x” and “y” represent the concentration of the target substance and the detected peak area, respectively.
[0104] Table 5 Precision and accuracy of ionic covalent organic framework solid phase microextraction-ultra-high performance liquid chromatography-tandem mass spectrometry for the detection of neurotransmitters in brain tissue
[0105]
[0106] “*” represents the spiked concentrations of low, medium and high levels, which are 50, 500 and 1000 μg / mL respectively; “#” represents the spiked concentrations of low, medium and high levels, which are 50, 500 and 1000 ng / mL respectively.
[0107] Example 10: In situ extraction and analysis of neurotransmitters in different brain regions of mice by SPME combined with HPLC-MS / MS
[0108] SPME in situ sampling analysis: Use the numbers engraved on the coronal sections of the mouse brain marked on the slice mold (brain) (coronal section, suitable for mouse brain, slice thickness 1mm) and combine with the mouse brain atlas to determine the area of the mouse brain. The intersection of the inferior sulcus line of the number 4 and the sagittal midline is used as the location of the anterior fontanelle, and the mouse brain is divided into seven areas. After the mouse brain is fixed in the mold, SPME in situ static sampling analysis is performed on the prefrontal cortex area (3-4), hippocampus area (6-7) and cerebellum area (9-11). When the mouse brain has not been completely thawed, insert the solid phase microextraction fiber coating into the positioned mouse brain tissue and adjust its depth appropriately. Static extraction for 40 minutes, remove the fiber. Wipe off the brain tissue and other debris on the surface of the solid phase microextraction fiber with dust-free paper, and then rinse the fiber with mass spectrometry grade water for 10 seconds. The neurotransmitters adsorbed on the SPME fiber were desorbed by oscillation using 100 μL of a 1% FA+H2O / ACN / MeOH (4:3:3, v / v / v) mixed solvent. After desorption for 10 min, the SPME fiber was removed and the eluted solution was subjected to UPLC-MS / MS analysis.
[0109] The established method was used to test the contents of various neurotransmitters in the prefrontal cortex, hippocampus and cerebellum of the normal group mice and the depression model group mice. The specific results are shown in Table 6. Compared with the normal control group, the concentration levels of neurotransmitters in different brain regions of the depression model group were mostly decreased. The concentrations of neurotransmitters in the three brain regions of the prefrontal cortex, hippocampus and cerebellum were analyzed. The results showed that most of these neurotransmitters were mainly concentrated around the hippocampus, followed by the prefrontal cortex of the mouse brain.
[0110] Table 6 Results of neurotransmitter analysis in different brain regions of mice
[0111]
[0112] Example 11: Analysis of neurotransmitters in actual mouse serum samples by SPME combined with UPLC-MS / MS
[0113] Take 200 μL of mouse serum sample and dilute it to 1 mL with PBS buffer and place it in a sample injection vial. Then immerse the prepared SPME fiber coating end in the diluted serum sample. After oscillating and extracting for 30 minutes, wash the SPME fiber with ultrapure water for 10 seconds to remove impurities such as inorganic salts and insoluble pollutants on the surface. Subsequently, 100 μL of 1% FA+H2O / ACN / MeOH (4:3:3, v / v / v) mixed solvent was used to oscillate and desorb the neurotransmitters adsorbed on the SPME fiber. After desorption for 10 minutes, the SPME fiber was removed and the eluted solution was analyzed by UPLC-MS / MS. The established method was used to test the content of various neurotransmitters in the serum of normal mice and depression model mice. The specific results are shown in Table 7. As can be seen from the results in Table 7, by comparing the NTs in the serum of each group of mice, the concentration levels of 19 neurotransmitters in the serum of depression model mice were significantly lower than those in the normal group, except for the abnormal content of individual neurotransmitters caused by individual differences in mice, especially monoamine neurotransmitters, which is consistent with the monoamine deficiency hypothesis related to depression.
[0114] Table 7 Analysis results of neurotransmitters in actual mouse serum samples
[0115]
[0116] The basic principles, main features and advantages of the present invention are shown and described above. It should be understood by those skilled in the art that the present invention is not limited by the above embodiments. The above embodiments and the contents described in the specification are only used to illustrate the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements. These changes and improvements all fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
[0117] The above contents are only preferred embodiments of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. An application of an ionic covalent organic framework material in preparing an adsorbent for sample pretreatment, characterized in that: The ionic covalent organic framework material is obtained by using ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol as functional monomers and acetic acid as a catalyst through Schiff base reaction condensation.
2. The use according to claim 1, characterized in that: The specific preparation method of the ionic covalent organic framework material is: accurately weigh ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol, mix, then add a reaction solvent, then add an acetic acid solution, and ultrasonically disperse; then, degas and seal through a freeze pump-thaw cycle, and react; after the reaction is completed, cool to room temperature, collect the precipitate by centrifugation, wash and dry to obtain the ionic covalent organic framework material.
3. The use according to claim 2, characterized in that: The molar ratio of ethidium bromide, 2,5-diaminobenzoic acid and trialdehyde phloroglucinol is 0.8-1.2:0.8-1.2:1.2-1.
8.
4. The use according to claim 2, characterized in that: The concentration of the acetic acid solution is 6 M, and the ratio of the acetic acid solution to trialdehyde phloroglucinol is 0.5 mL:0.45 mmoL.
5. The use according to claim 2, characterized in that: The reaction temperature is 110-120° C., the reaction time is 60-72 hours, and the reaction solvent is a mixed solution of 1,3,5-trimethylbenzene and 1,4-dioxane in a volume ratio of 2:
3.
6. The use according to claim 1, characterized in that: Sample preparation included extraction analysis of neurotransmitters in serum samples and brain tissue.
7. An application of an ionic covalent organic framework solid phase microextraction fiber as an adsorbent in sample pretreatment, characterized in that: The fiber is based on nickel-titanium fiber filaments, and is self-assembled layer by layer through a sol-gel coating method, and an ionic covalent organic skeleton material is coated on the fiber filaments to obtain an ionic covalent organic skeleton solid phase microextraction fiber.
8. The use according to claim 7, characterized in that: The preparation of the ionic covalent organic framework solid phase microextraction fiber specifically includes the following steps: (1) Preparation of PAN glue: Weigh 4.5-5.0 g PAN and 72.5 mL N,N-dimethylformamide, mix, stir evenly, and seal. (2) weighing 300.0-325.0 mg of the ionic covalent organic framework material, then adding 2.5-3.1 g of PAN glue, and then adding 0.15-0.2 g of propylene glycol, vortexing, and then stirring overnight to obtain an ionic covalent organic framework solid phase microextraction fiber coating; (3) The ionic covalent organic framework solid phase microextraction fiber coating is coated on the fiber filament to obtain the ionic covalent organic framework solid phase microextraction fiber.
9. The use according to claim 8, characterized in that: The temperature of the sealed storage in step (1) is 90° C. and the time is 1 hour.
10. The use according to claim 7, characterized in that: Sample preparation included extraction analysis of neurotransmitters in serum samples and brain tissue.
Citation Information
Patent Citations
Mixed matrix anionic membrane and manufacturing method thereof
CN109546191A
Organic porous material with mixed ion skeleton structure, film material and preparation method
CN113461889A
Preparation method and application of ionic covalent organic framework membrane material
CN115814601A
Preparation method and application of asymmetric self-supporting covalent organic framework film
CN117946355A
Tailored covalent organic framework membranes for lithium extraction and recycling
WO2023073669A1
Cited By
Preparation method and application of three-component covalent organic framework (T / 4E-COF) photocatalyst
CN122164492A